2012
DOI: 10.1002/pola.26347
|View full text |Cite
|
Sign up to set email alerts
|

Living cationic polymerization of vinyl ethers with a naphthyl group: Decisive effect of the substituted position on naphthalene ring

Abstract: Living cationic polymerization of a vinyl ether with a naphthyl group [2‐(2‐naphthoxy)ethyl vinyl ether, βNpOVE] was achieved using base‐assisting initiating systems with a Lewis acid. The Et1.5AlCl1.5/1,4‐dioxane or ethyl acetate system induced the living cationic polymerization of βNpOVE in toluene at 0 °C. The living nature of this reaction was confirmed by a monomer addition experiment, followed by 1H NMR and matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The naphthyl group was expected to function as a Friedel–Crafts‐type quencher because of its high nucleophilicity. We have previously demonstrated that a well‐defined poly(βNpOVE) could be synthesized by a base‐assisting living cationic polymerization with the IBEA/Et 1.5 AlCl 1.5 initiating system …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The naphthyl group was expected to function as a Friedel–Crafts‐type quencher because of its high nucleophilicity. We have previously demonstrated that a well‐defined poly(βNpOVE) could be synthesized by a base‐assisting living cationic polymerization with the IBEA/Et 1.5 AlCl 1.5 initiating system …”
Section: Resultsmentioning
confidence: 99%
“…More reactive aromatic rings such as a naphthyl group could allow more facile synthesis of well‐defined polymers in cationic polymerization. Thus, we started investigating precision synthesis via cationic polymerization of naphthyl‐containing monomers, and have reported the living cationic polymerization of monomers with a naphthyl ring, despite its high reactivity in the electrophilic substitution reactions owing to more expanded conjugated system than a phenyl ring …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(vinylnaphthalenes) have become of interest owing to their potential applications as fluorescence tags and electron beam lithography resists as well as their interesting photophysical characteristics . However, the well‐controlled polymerization of vinylnaphthalene derivatives remains challenging since the uneven electron density distribution makes naphthalene highly susceptible to nucleophilic reagents and Friedel–Crafts reaction . Therefore, the polymerization of vinylnaphthalene monomers encounters great difficulty via cationic, anionic, and radical mechanisms .…”
Section: Methodsmentioning
confidence: 99%
“…The coordination polymerization of 1VN was first examined at room temperature by using precursor 1 based catalytic system (Figure ) and a moderate activity was observed (1.44 × 10 5 g (mol Ln h) −1 ; Table 1 , run 1) although the catalyst show extremely high activity and syndio‐selectivity for styrene polymerization . Unexpectedly, the GPC curve of the resulting product gives pronounced multimodal peaks with a very broad molecular weight distribution (PDI = 54.9; Table , run 1; Figure ; Figure S26, Supporting Information), which was probably caused by addition‐alkylation reactions because of the high reactivity of naphthalene ring to the strong Lewis acidic active species . The pyridyl side‐armed fluorenyl scandium precursor 2a , a highly active and syndioselective catalyst for styrene polymerization also, was employed to initiate 1VN polymerization.…”
Section: Methodsmentioning
confidence: 99%